Cracking behavior of full-scale pre-tensioned prestressed concrete double-Tee members with steel-wire meshes. (December 2021) - Yao, Gangfeng; Xiong, Xueyu; Ge, Yipeng
Abstract: Prestressed concrete double-Tee (PCDT) members are widely used in short-to-medium span structures, such as bridges, parking structures, industrial plants and warehouses. To closely investigate the cracking behavior of PCDT members with steel-wire meshes, four full-scale specimens with different spans and amount of prestress tendons were tested under monotonic loading in this paper. The distribution, number and width of cracks were presented in detail. It could be found that distribution of cracks was dense and uniform, and crack widths of PCDT members were more scatter than ordinary reinforcement concrete (RC) members. Moreover, a comparative study of maximum crack widths predicted respectively by Eurocode 2 and Chinese codes was carried out. Results showed that maximum crack widths calculated by Eurocode 2 were a little bit conservative and relatively agreed well with test results. In addition, the Chinese codes underestimated the test results, especially when the stress of non-prestress steel was lower than 200 MPa, which would be unsafe for the design. Highlights: Four full-scale prestressed concrete double-tee (PCDT) members with steel-wire meshes were tested under monotonic load in this paper. The detailed test results of cracking performance of the PCDT specimens were presented, including the distribution of cracks, number of cracks, mean crack width and maximum crack width. A comparative study of maximum crack width predicted respectively by Eurocode 2 and Chinese codes was carried out with the experimental results and some design recommendations were provided.